The role of microglial exosomes in brain injury - Chen, Yahong; Zhu, Jie; Ji, Jingjing; Liu, Zhifeng; Ren, Guangli (Frontiers in Cellular Neuroscience, 2022)
Microglia are involved in the physiological and pathological processes of nervous system. In addition, exosomes derived from microglia are also involved in the immune response of the central nervous system. However, their specific mechanism is still unknown. We elucidated microglial exosome characteristics, release patterns, pro-proliferative and pro-apoptotic effects on neurons and other glial cells, immunomodulatory effects and regulation of the extracellular microenvironment. Understanding the relationship between microglia exosomes and brain injury can provide new targets for clinical treatment.